Disentangling Challenges to Scaling Alternate Wetting and Drying Technology for Rice Cultivation: Distilling Lessons From 20 Years of Experience in the Philippines - Enriquez, Yuji; Yadav, Sudhir; Evangelista, Gio Karlo; Villanueva, Donald; Burac, Mary Ann; Pede, Valerien (Frontiers in Sustainable Food Systems, 2021)
Alternate wetting and drying (AWD) is a low-cost innovation that enables farmers to adapt to increasingly poor irrigation conditions (such as drought), increase overall farm production efficiency, and mitigate greenhouse gas emissions. It is seen as a pathway for transforming agri-food systems into more resilient, productive, biologically diverse, and equitable forms, ensuring our commitments to the UN Sustainable Development Goals (SDGs). This paper uses scaling-up and innovation uncertainty frameworks to review the success and challenges of AWD's 20-year scaling trajectory in the Philippines and explain the key factors that have influenced its outcomes. The framework adapted for this study is also used to examine the fitness between the scaling context and requirements, organizational mission, and corresponding capabilities. Findings show the innovation platform that vertically integrated key actors and locally adapted AWD has helped foster essential breakthroughs in creating an enabling environment that took AWD to national policy adoption in the Philippines. However, the dominant focus on technology transfer, product focus, and preference for controlled environments in the scaling practice has neglected many important contextual factors, allowing mismatches in enabling policy incentives, institutions, and scale to diminish the impacts of AWD in gravity-based systems. Our findings suggest that rethinking and re-envisioning the ways in which the impact can be scaled in irrigation rice systems using AWD is critical to sustaining food security and making the agriculture sector more resilient to climate change.